Filmes e revestimentos do Caranguejo-Uçá (Ucides cordatus) com aplicação em postas de serra (Scomberomorus brasiliensis) congeladas. - Vale, Diego Alves do (2017)
The fish industry generates wastes that negatively impact the environment. Providing solutions that minimize these impacts has become an interesting alternative in the last decades. Crab residues contain chitin in their chemical composition, which through the deacetylation process chitosan is obtained. One of the ways of using chitosan in the food industry is the formulation of films and edible coatings in order to prolong the shelf life of food products. The objective of this study was to produce films and edible coatings based on chitosan extracted from Uçá-crab (Ucides cordatus) for subsequent application on frozen Serra Spanish mackerel fillets (Scomberomorus brasiliensis). The films produced were characterized by water vapor permeability, solubility, color and opacity and mechanical properties. The antimicrobial activity of coating solutions was evaluated against four strains of psychotropic bacteria. The scattering coefficient served as a criterion in the choice of the best coating solution to be applied on frozen Serra Spanish mackerel fillets. Evaluations of fish quality parameters such as physico-chemical and microbiological analyzes as well as evaluation of fish, coating and glaze weight losses were carried out. The results showed that films containing 2.0% of chitosan (w/v) 0.6% of glycerol (v/v) presented good mechanical properties and protection against ultraviolet rays (darker films) without significantly altering the properties of opacity, water vapor permeability and solubility when compared to other chitosan and glycerol concentrations studied. Although all concentrations of chitosan coatings showed antimicrobial activity against the four strains of bacteria tested, the results showed that the lower the chitosan concentration the greater the antibacterial activity. The coating solution of 2.0% chitosan (w/v) and 0.6% of glycerol (v / v) was selected for application on frozen Serra Spanish mackerel fillets due to its good spreading coefficient. The chitosan coating presented lower weight loss than glaciation. Moreover, the chitosan coating presented better results in relation to the pH, nitrogen of the total volatile bases, reactive substances to thiobarbituric acid and antimicrobial activity. Therefore, the chitosan-based coatings presented potential as edible coatings, prolonging the shelf life of frozen Serra Spanish mackerel fillets (Scomberomorus brasiliensis).